ASSESSING VIRTUAL REALITY MEDIA PRODUCTIONS: Findings from a Qualitative Analysis of Immersive Experiences in Climate Change as Offered via Oculus TV (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
This study explores virtual reality (VR) uses in climate change storytelling. The study uses a mixed approach, i.e., qualitative content analysis, experiential media (EM) theoretical model, and the United Nation’s Intergovernmental Panel on Climate Change special report’s framework on the climate crisis. This study looks at nine different VR media productions on climate change available on the Oculus TV, a VR application by Meta Platforms Inc (formerly Facebook Inc). The nine VR media productions observation and experience involved the use of Oculus Quest 2 Head-Mounted Display (HMD) to understand: 1) to what extent do the VR media productions utilize six qualities of EM; 2) what themes do such VR media productions highlight pertaining to climate change, and 3) to what extent do such themes capture key points highlighted by the landmark IPCC 2018 special report’s framework. The findings revealed that all the nine VR media productions utilized limited qualities of EM, i.e., (1) interactivity, (2) immersion, (3) multisensory presentation, (4) algorithm and data, (5) first-person perspective, and (6) natural user interface. The findings also revealed five broad thematic categories, including global warming; biodiversity & endangered species; culture & traditions; conservation & disaster management; and agriculture, along with various sub-themes identified from all the nine VR media productions. The thematic analysis showed that the VR media productions utilized limited framing and contextualization of the issues pertaining to climate change — as opposed to the multidisciplinary approach that the IPCC report takes and offers as a framework to help people understand the gravity of the problem caused by climate change. The study extends the theoretical understanding of the role VR plays in highlighting the climate crisis and provides practical implications on the uses of VR for climate change storytelling and reporting. To cite this article (7th APA style): Iyer, S. R. (2022). Assessing virtual reality media productions: Findings from a qualitative analysis of immersive experiences in climate change as offered via Oculus TV. Journal Communication Spectrum: Capturing New Perspectives in Communication 12(2), 77-95. https://doi.org/10.36782/jcs.v12i2.2284